CRIME AND GLOBALIZATION: REFLECTIONS ON TRANSNATIONAL CRIMES AND INTERNATIONAL LEGAL COOPERATION IN CONTEMPORANEITY - Caíque Ribeiro Galícia (Revista Eletrônica de Direito Processual, 2018)
The present work presents some considerations about the manifestation of the phenomenon of globalization and its interferences in the dynamics of a new form of crime, denominated transnational. In this panorama, after this first step, it exposes the main conceptual contours about international legal cooperation in criminal matters, since it is the procedural tool useful to fulfill the purpose of the criminal prosecution, allowing both the collection of data for prosecution and assuring the fundamental rights of the accused . In this way, the main objective was to present the conceptual standards of the institutes mentioned, allowing the development of new scientific research guidelines for the theme. Methodologically the work was oriented from the bibliographical analysis from a complex and transdisciplinary view.